Use of sorghum-based distillers grains in diets for nursery and finishing pigs - B W Senne; I Mavromichalis; S L Johnston; P S Sorrell; I H Kim; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1996)
Two experiments were conducted to etermine the effects of sorghum-based distillers dried grains with solubles in isocaloric diets for nursery and finishing pigs. Rate and efficiency of gain in nursery pigs were decreased with 45% or more distillers grains. For finishing pigs, efficiency of gain was improved as distillers grains was increased to 60% of the diet, and carcass fatness was increased by about .1 inch at the highest concentration.; Swine Day, Manhattan, KS, November 21, 1996
Keywords: Swine day; 1996; Kansas Agricultural Experiment Station contribution; no. 97-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 772; Swine; Distillers grains; Nursery pigs; Finishing; Sorghum